POLA PENANGANAN KONFLIK AKIBAT KONVERSI AGAMA DI KALANGAN KELUARGA CINA MUSLIM - Elizabeth, Misbah Zulfa (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2013)
This research has the purposes to reveal the patterns of conflict caused by religious conversion among Chinese Muslim in Semarang, the patterns of conflict resolution applied among them, and their view on the conflict resolutions applied. Applying the methods of interviewing using structured interview guidance, participation observation, and deep interview, it was revealed that there are five kinds of conflict come out of conversion: indifference, teasing allusion, rude speaking, rejection, and hostile. Meanwhile there are three ways found in resolving conflict caused by religious conversion: to let the conflict goes on and resolved by time, to explain the problem related to Islam, and to go out from family circle. Based on the varieties in resolving the conflict, it is revealed that the community tends to approve the peace way in solving any problem, otherwise it will break the value the community hold, harmony.***Penelitian ini bertujuan untuk mengungkap pola konflik yang disebabkan oleh konversi agama di kalangan Cina Muslim di Semarang, pola resolusi konflik yang diterapkan di kalangan mereka, serta pandangan mereka mengenai penyelesaian yang mereka lakukan, Dengan menggunakan metode wawancara dengan pedoman wawancara terstruktur, observasi partisipasi, observasi, dan wawancara mendalam ditemukan bahwa ada lima bentuk konflik akibat konversi: tidak dipedulikan, digoda, bicara kasar, penolakan, dan permusuhan. Sementara itu ditemukan tiga cara penyelesaian konflik, yaitu membiarkan masalah sehingga hilang bersama waktu, menjelaskan tentang Islam, dan keluar dari lingkup keluarga. Berdasarkan keragaman cara penyelesaian masalah tampak bahwa komunitas Cina cenderung menggunakan cara damai dalam menyelesaikan masalah.